PROFIL PEMECAHAN MASALAH SPLTV SISWA KELAS X SMA NEGERI 1 BANAWA TENGAH DITINJAU DARI KEMAMPUAN MATEMATIKA: Profil of SPLTV Problem OF Student Class X SMA Negeri 1 Banawa Tengah Review Through Ability in Mathematics - Mifrahwanti, Titania; Nurhayadi; Rizal, Muh. (Jurnal Elektronik Pendidikan Matematika Tadulako, 2023)
This study aims to obtain a description of the problem solving profile of SPLTV students of class X SMA Negeri 1 Banawa Tengah in terms of mathematical ability. This study uses a qualitative method with a qualitative descriptive approach. The research subjects were 3 students, namely students who had high, medium and low mathematical abilities based on the problem solving steps proposed by Polya. The results obtained indicate that: (1) Students who have high mathematical abilities use all stages of Polya in solving SPLTV problems. (2) Students who have moderate mathematical ability have not been able to use all of Polya's stages in solving SPLTV problems, the stages in question are in the re-examination stage. However, the subject gives his opinion by explaining using his own language why not re-examine the results of the completion of the given problem. (3) Students who have low mathematical abilities have not been able to go through all the stages of Polya in solving problems, the subject is only able to go through the stage of understanding the problem but the subject needs to read and pay attention to the information on the problem repeatedly.